Loaded notched dual compact rectangular ultra-wideband applications monopole antenna - Sahar Kareem Hassan; Adheed Hasan Sallomi; Musa Hadi Wali (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
This work presents a rectangular of microstrip ultra wideband patch antenna for worldwide interoperability for microwave access (Wi-Max) and wireless local area network (WLAN) with a dual band-notched feature. The planned an antenna consists the rectangular of patch antenna with the largely deficient of ground structure. Through inserting slots in the radiating patch, dual notch characteristics may be produced. The suggested antenna is 20×30×1.6 mm3 in volume. The first notch, made by slots operating at the first notch, produced by slots running at 3.5 GHz, for Wi-Max (from 3.3-3.7 GHz), while of a second, created by slots operating at 5.5 GHz, for WLAN (from 5.1-5.8 GHz). An antenna covers the whole ultra-wideband frequency range (3.1-10.6 GHz). Computer simulation technology (CST) 2021 simulation software used for simulate proposed of antenna. A simulated antenna’s emission pattern is almost omnidirectional, and the recommended antenna’s gain is approximately constant over the ultra-wideband (UWB) spectrum, excluding notch areas.